Hydrodynamics and Aquatic Vegetation Drive Spatial Patterns of Environmental DNA in Ponds - Sandra R. Mayne; Jeffrey A. Manning; Stephen M. Henderson; Meghan B. Parsley; Katherine M. Strickler; Jeffrey R. Nielson; Caren S. Goldberg (Environmental DNA)
ABSTRACT Environmental DNA (eDNA) sampling is a powerful method for detecting aquatic species at low densities. However, eDNA may remain close to the source in lentic systems, decreasing the effectiveness of eDNA surveys. We conducted cage experiments with salamanders and simultaneous detailed hydrologic and wind measurements to investigate the influence of the physical environment on detection patterns of eDNA in ponds. We found much higher detection rates in the surface layer than at depth, and that aquatic vegetation reduced detection of eDNA produced in open water by 80%–94%. Within the surface mixed layer, detection rates were highest close to the source in the direction of water flow in the bottom half of the layer, and detections farthest from the source occurred when velocities in this sublayer were high. Detections were near zero even close to the source when this sublayer was flowing fast and away from the sampling point. The direction of water flow in this lower half of the surface mixed layer was negatively correlated with wind direction for most of the study. These spatial and temporal dynamics indicate that eDNA transport processes in ponds are highly complex. Sampling away from aquatic vegetation, in the surface mixed layer, and upwind of potential sources, in addition to sampling at many locations within a pond and considering temporal patterns, may improve detection of rare pond species. This work contributes to a growing body of literature characterizing the variability of eDNA detection in lentic systems.